Safeguard against DNA sensing: the role of TREX1 in HIV-1 infection and autoimmune diseases - Hasan, Maroof; Yan, Nan (Frontiers in Microbiology, 2014)
Innate immune recognition is crucial for host responses against viral infections, including infection by human immunodeficiency virus 1 (HIV-1). Human cells detect such invading pathogens with a collection of pattern recognition receptors (PRRs) that activate the production of antiviral proteins, such as the cytokine interferon-type I, to initiate antiviral responses immediately as well as the adaptive immune response for long-term protection. To establish infection in the host, many viruses have thus evolved strategies for subversion of these mechanisms of innate immunity. For example, acute infection by HIV-1 and other retroviruses have long been thought to be non-immunogenic, signifying suppression of host defenses by these pathogens. Studies in the past few years have begun to uncover a multifaceted scheme of how HIV-1 evades innate immune detection, especially of its DNA, by exploiting host proteins. This review will discuss the host mechanisms of HIV-1 DNA sensing and viral immune evasion, with a particular focus on TREX1, a host 3’ to 5’ exodeoxyribonuclease (also known as DNase III).